2020
DOI: 10.3390/app10124259
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Augmented Reality in the Automotive Industry: A Systematic Literature Review

Abstract: Augmented reality (AR) is a fairly new technology enabling human machine interaction by superimposing virtual information on a real environment. Potential applications can be found in many areas of research from recent years. This study presents a systematic review of existing AR systems in the automotive field, synthesizing 55 studies from 2002 to 2019. The main research questions are: where AR technology has been applied within the automotive industry, what is the purpose of its application, what are the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 84 publications
1
21
0
Order By: Relevance
“…Thus, it was concluded that AR technology might have a future potential in helping and training operations in industrial setting and the workplace. This will increase the workers' efficiency, by reducing the cognitive load and the working time [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was concluded that AR technology might have a future potential in helping and training operations in industrial setting and the workplace. This will increase the workers' efficiency, by reducing the cognitive load and the working time [48].…”
Section: Discussionmentioning
confidence: 99%
“…The quality appraisal (QA) procedure included the investigation of the quality of the selected studies relevant to the main research topic, to assist the analyses and synthesis process [48]. All authors carefully monitored the planned review progress and the task allocation to maintain the elevated quality of the SLR.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In addition, the virtual warning also suggests to the driver the appropriate time to begin a safe overtaking maneuver based on the lateral position of the cyclist in the lane. From a practical point of view, the implementation of this AR system on board could exploit head-up display (HUD) technology (e.g., 32, 33 ), consisting of an electronic system capable of superimposing vehicle information on the windscreen without the driver having to take their eyes off the road. HUD allows drivers to keep their attention focused on the road while receiving information that would normally require a glance at the dashboard.…”
Section: Methodsmentioning
confidence: 99%
“…A very systematic review papers can be seen in [19][20][21] works. In all of these works, the common points are that AR has a lot of previous works showing tracking and registering applications in most of the market sectors.…”
Section: State Of the Artmentioning
confidence: 99%